IMPLEMENTASI DAN ANALISA PERFORMANSI LAYANAN VPN PADA JARINGAN MPLS-TE MENGGUNAKAN PROTOKOL BGP DENGAN METODE QOS INTSERV - Salsa Rizkiana; Doan Perdana; Ridha Negara (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2017)
The Traffic Engineering feature on MPLS can move a traffic link that has congestion avoidance, therefore a link can be moved to an empty link. The MPLS VPN TE technology is the solution in increasing security and choosing the best route in a network. Integrated service is one of a QoS model for bandwidth controlling problem on a network that is needed for MPLS VPN-TE technology for stability of network. Open IMS Core is a multimedia service server that is used on MPLS VPN TE technology by considering Quality Of Service on multimedia. The usage of BGP protocol is a type of routing that is expected to do an exchange of routing information by mapping an IP table network inter-Autonomous System by giving Qos enhancement on a network In this research, the author implements MPLS VPN TE on Mikrotik Router. The test result of Traffic Engineering feature on MPLS VPN network show improved 27,44 % in delay for Voip services, 11,14% for video call services. For Throughput parameter showed a improved 6,02% for Voip service, 56,6 for video call services. For jitter parameters result < 1ms.